2009
DOI: 10.1161/circulationaha.108.832444
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Variability of Internal Mammary Artery Graft Use in Contemporary Multivessel Coronary Artery Bypass Graft Surgery

Abstract: Background-Use of an internal mammary artery (IMA) is a well-recognized, nationally endorsed quality indicator for evaluating the process of operative care for coronary artery bypass graft surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(124 citation statements)
references
References 33 publications
(31 reference statements)
2
121
0
1
Order By: Relevance
“…[17][18][19][20][21] However, bilateral internal-thoracic-artery grafting has not been widely adopted because of three main factors: it is a more complex procedure, it is associated with a higher risk of sternal wound complications, and there is a lack of randomized evidence of benefit. [22][23][24] The Arterial Revascularization Trial (ART) was initiated in 2004 to address these concerns. 25 The primary objective of the trial was to compare 10-year survival rates associated with bilateral and single internal-thoracic-artery grafting, and secondary outcomes included clinical events, quality of life, and health economic measures.…”
mentioning
confidence: 99%
“…[17][18][19][20][21] However, bilateral internal-thoracic-artery grafting has not been widely adopted because of three main factors: it is a more complex procedure, it is associated with a higher risk of sternal wound complications, and there is a lack of randomized evidence of benefit. [22][23][24] The Arterial Revascularization Trial (ART) was initiated in 2004 to address these concerns. 25 The primary objective of the trial was to compare 10-year survival rates associated with bilateral and single internal-thoracic-artery grafting, and secondary outcomes included clinical events, quality of life, and health economic measures.…”
mentioning
confidence: 99%
“…One example is provided by Tabata and colleagues regarding the use of the IMA graft in multivessel CABG surgery [63]. Since use of the IMA graft has been repeatedly shown to be associated with significantly improved short-term and long-term survival in CABG, it is encouraging to see the frequency of IMA use in CABG surgery to be increasing.…”
Section: Application Of Performance Measures For Reporting Qualitymentioning
confidence: 99%
“…Since use of the IMA graft has been repeatedly shown to be associated with significantly improved short-term and long-term survival in CABG, it is encouraging to see the frequency of IMA use in CABG surgery to be increasing. However Tabata's study shows that many patients do not receive the benefits of IMA grafts, and some hospitals have a very low IMA use rate, which offers a significant opportunity for continued improvement [63].…”
Section: Application Of Performance Measures For Reporting Qualitymentioning
confidence: 99%
“…Specifically, patients who received two IMA grafts at initial surgery had approximately 10% risk for reintervention at 10 years; those with one IMA had 20% risk; and those with no IMA had approximately 30% risk for reintervention at 10 years [18]. However, the surgical community has not fully utilized these assets despite numerous, compelling data [19][20][21][22][23]. Jones succinctly summarized the decision point facing conventional, open surgery in the face of rapidly advancing technologies, particularly PCI, and the impact on referral trends for surgical intervention: " improve the long-term outcome, lessen resources used, or both."…”
Section: Are There Alternatives To Cabg Which Could Improve Long-termentioning
confidence: 99%
“…The demonstrated clinical advantages of BIMA grafting strategies include prolonged survival and reduced need for coronary reintervention on the basis of recurrent myocardial ischemia, including freedom from the need for coronary reintervention [15,88,90] which hold true for women as well as for men, where it has been demonstrated that use of BIMA had 3-fold improved cardiacrelated survival compared with patients who did not receive an IMA graft [91]. Reported rates of BIMA use in CABG range from 4.0% to nearly 50% depending upon several factors including the contributing authors' practice preferences and the particular patient cohort treated [19][20][21][22]92]. However, it has been estimated that up to 80% would be candidates for BIMA grafting [93].…”
Section: Bilateral Internal Mammary Artery Conduitsmentioning
confidence: 99%